Enhanced Photoredox Activity in Nitrogen‐Doped Carbon Nitride for Heterogeneous Nitrogen and Oxygen Radical Reactions - Lan Qin; Huan Liu; Yi Wei; Lian‐Qing Chen; Xiao‐Qiang Hu (Advanced Science)
Abstract A nitrogen‐doped carbon nitride (NCN) has been synthesized and utilized for the sustainable generation of reactive nitrogen and oxygen radicals under mild photocatalytic conditions. This material exhibits a significant improvement in the separation and transfer of photoexcited charge carriers, which facilitates the direct activation of N─H and O─H bonds to achieve a variety of radical carboamination, oxyamination and deoxygenation reactions. The NCN catalyst has further demonstrated its robust photoredox activity through several successful applications, including the aerobic oxidation of boronic acids and the controllable oxidation of alcohols to aldehydes and carboxylic acids. Moreover, the NCN catalyst maintains its reactivity and efficiency even after multiple cycles of use, showcasing its durability and potential for practical applications in sustainable chemistry.